2010
DOI: 10.1007/s11095-010-0132-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Corneal Permeability of Drug-Like Compounds

Abstract: The developed models are useful in early drug development to predict the corneal permeability and steady-state drug concentration in aqueous humor without experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 29 publications
2
30
0
Order By: Relevance
“…35,36 Primary cultured human corneal epithelial cells grown on permeable supports can address questions concerning drug transport mechanisms by avoiding species extrapolation and the influence of modified gene expression due to cell immortalization. 27,37 These model systems can be valuable for corneal penetration studies since they allow high sample throughput, access to both the apical and basolateral sides, and A to B and also B to A transport studies. 9,37 These models are desirable because they present an ethical alternative to in vivo experimentation, improve test accuracy and reproducibility, and allow testing with organotypic cultures derived from different donors, thus representing a large population, similar to that observed in clinical trials.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 Primary cultured human corneal epithelial cells grown on permeable supports can address questions concerning drug transport mechanisms by avoiding species extrapolation and the influence of modified gene expression due to cell immortalization. 27,37 These model systems can be valuable for corneal penetration studies since they allow high sample throughput, access to both the apical and basolateral sides, and A to B and also B to A transport studies. 9,37 These models are desirable because they present an ethical alternative to in vivo experimentation, improve test accuracy and reproducibility, and allow testing with organotypic cultures derived from different donors, thus representing a large population, similar to that observed in clinical trials.…”
mentioning
confidence: 99%
“…27,37 These model systems can be valuable for corneal penetration studies since they allow high sample throughput, access to both the apical and basolateral sides, and A to B and also B to A transport studies. 9,37 These models are desirable because they present an ethical alternative to in vivo experimentation, improve test accuracy and reproducibility, and allow testing with organotypic cultures derived from different donors, thus representing a large population, similar to that observed in clinical trials. 4,25 Thus, the development of in vitro reconstructed human corneas would serve an important, growing need.…”
mentioning
confidence: 99%
“…The rate of drug elim- 55 ination from the tear fluid is in the range of 0.5-1.0 min À1 , and it 56 has been shown that the drug absorption takes place during the 57 first 2-3 min after instillation [5][6][7]. However, the ocular bioavail- 58 ability is low; usually in the range of 0.1-5% [8,9]. This is due to the 59 ocular permeation barriers and short contact time that limits the 60 period that is available for drug absorption [8].…”
mentioning
confidence: 99%
“…Permeability in 304 the relative open mucin layer structure is probably higher than 305 drug permeability in the cell layer, and mucin layer may not con-306 tribute significantly on overall drug permeation. Corneal 307 permeability in ex vivo rabbit cornea shows 407-fold permeability 308 range for small molecules [58]. Decreased hydrogen bonding and 309 increased logD values explain the increased permeability asso-310 ciated with the chemical structure [58].…”
mentioning
confidence: 99%
See 1 more Smart Citation